2014
DOI: 10.1097/mph.0000000000000039
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Corticosteroid-induced Osteonecrosis in Children Undergoing Chemotherapy for Acute Lymphoblastic Leukemia

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
3
24
2
1
Order By: Relevance
“…The findings of our study indicate that the frequency of ON correlates well with age 10 years or older and IR/HR protocol but not with sex. Our result is in accordance with that reported by Girard et al but diverges from that reported by Hyakuna et al and the Winkle et al, who noted that females aged 10 years and older are at a higher risk for ON and that the risk of ON should be considered when administering dexamethasone as part of the ALL treatment protocol for females aged 10 years and older . The pathogenesis and impact of sex on the development of ON remain unclear and require further investigation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of our study indicate that the frequency of ON correlates well with age 10 years or older and IR/HR protocol but not with sex. Our result is in accordance with that reported by Girard et al but diverges from that reported by Hyakuna et al and the Winkle et al, who noted that females aged 10 years and older are at a higher risk for ON and that the risk of ON should be considered when administering dexamethasone as part of the ALL treatment protocol for females aged 10 years and older . The pathogenesis and impact of sex on the development of ON remain unclear and require further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…Lower frequencies have been reported by other studies, such as that by Hyakuna et al, who reported an overall ON incidence of 1.5% (16/1095). Studies in Europe and the United States have shown highly variable results (1% to 2% up to 9%), depending on patient characteristics and treatment intensity . Strauss and Burger reported an estimated cumulative incidence of symptomatic ON in newly diagnosed ALL patients of 3.4% at eight years, while in our study, the cumulative incidence at five years was 11.96 ± 0.13.…”
Section: Discussioncontrasting
confidence: 52%
“…BCP‐ALL was then diagnosed at the age of 15 years. She was treated using a modified high‐risk protocol of the Japanese Children's Cancer and Leukemia Study Group 2004 without excess toxicity . Although she requires estrogen replacement due to ovarian dysfunction, she has been in continuous remission for 12 years since the diagnosis of ALL.…”
Section: Resultsmentioning
confidence: 99%
“…Additional risk factors for ON include age >10 years, obesity, Caucasian race, treatment intensity and asparaginase use (Mattano et al 2000 ;Niinimaki et al 2007 ;Kawedia et al 2011 ). While many children treated for ALL have evidence of ON on magnetic resonance imaging (MRI), symptomatic ON incidence is <20 % (Mattano et al 2000 ;Kawedia et al 2011 ;Hyakuna et al 2014 ).…”
Section: Osteonecrosismentioning
confidence: 99%